Assessment of gap areas of root filling techniques in teeth with 3D-printed different configurations of C-shaped root canals: a micro-computed tomography study - Gok, Tuba; Gok, Adem; Aciksoz, Haydar Onur (Bmc, 2025)
Background: Three-dimensional filling of root canals is important for the success of endodontic treatment. The complexity and differences in root canal anatomy in C-shaped canals lead to difficulties in endodontic procedures and make it difficult to compare root canal filling techniques reliably. This study aimed to evaluate the percentage of gap areas of different root canal filling techniques in 3D-printed C2 and C3-shaped root canals using micro-computed tomography (micro-CT). Methods: Root canals of two human mandibular molars in C2 and C3 configurations were prepared and scanned with micro-CT. Forty replicas (80 in total) were produced from each configuration using a 3-dimensional (3D) printer. C2 and C3 groups were divided into 4 groups according to filling techniques (n = 10); core carrier (CC), cold lateral compaction (CLC), continuous wave obturation (CW) and single cone technique with calcium silicate-based sealer (SC-CSS). Root canals were filled and scanned with micro-CT. The gap areas in the apical, middle and coronal thirds were calculated as percentages. The one-way ANOVA test was used to evaluate the percentages of gap areas and Tukey's test for multiple comparisons. Results: In C2-shaped canals, SC-CSS group showed a statistically higher percentage of gap areas in the apical third (p <.05), there were no significant differences among other groups (p >.05). In the middle part, there were no significant differences among groups (p >.05). The CW group showed a significantly lower percentage of gap areas in the coronal third than other groups (p <.05). In C3-shaped canals, SC-CSS group showed statistically higher percentage of gap areas in apical third (p <.05), CC and SC-CSS groups showed lower percentage areas in the middle part compared to CLC and CW groups (p <.05) and there was no difference between among groups in the coronal third (p >.05). Conclusions: The SC-CSS technique showed more gap areas in the apical region of C2 and C3-shaped canals. Considering any root canal filling technique in clinical practice, the compaction of filling material in the large volume canals of the C-shaped root canal system is necessary to reduce gap areas.
Keywords: 3D printing; C-shaped root canal; Gap area; Micro-computed tomography; Root filling technique